2017
DOI: 10.1042/cs20171053
|View full text |Cite|
|
Sign up to set email alerts
|

Biomarkers of disease can be detected in mice as early as 4 weeks after initiation of exposure to third-hand smoke levels equivalent to those found in homes of smokers

Abstract: Third-hand smoke (THS) is a newly discovered environmental health hazard that results from accumulation and aging of second-hand smoke (SHS) toxins on surfaces where smoking has occurred. Our objective was to determine whether there is a time-dependent effect of THS exposure on health. Using an in vivo exposure mouse system that mimics exposure of humans to THS, we investigated its effects on biomarkers found in serum, and in liver and brain tissues. Mice were exposed to THS for 1, 2, 4, or 6 months and brain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
0
24
0
4
Order By: Relevance
“…In our previous time-dependent study, the brain takes much longer (4 months) for THS exposure with the 40 cigarette-smoking regimen to result in the accumulation of H 2 O 2 (Adhami et al, 2017). We speculate that the blood-brain barrier is most likely the reason why the brain is more "protected" from THS exposure and molecular damage takes longer to occur.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In our previous time-dependent study, the brain takes much longer (4 months) for THS exposure with the 40 cigarette-smoking regimen to result in the accumulation of H 2 O 2 (Adhami et al, 2017). We speculate that the blood-brain barrier is most likely the reason why the brain is more "protected" from THS exposure and molecular damage takes longer to occur.…”
Section: Discussionmentioning
confidence: 77%
“…For all of the studies shown here, we investigated levels of molecules that had shown to be altered in our previous studies of the timedependent effect of THS exposure (Adhami et al, 2017). We chose to determine whether those same molecules were altered in a dose-dependent manner in the serum, and liver and brain tissues of different cohorts of mice exposed for 2 month to doses of THS generated by the 10, 20 and 40 cigarette-smoking regimen and tested these mice against 13 BMH (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…dusts) and dermal uptake from contact with contaminated surfaces and clothes/textiles, as well as ingestion from the hands or food that are exposed to tobacco smoke 7 . Negative health impacts of THS exposure on rodents have been recently revealed 8,14 ; however, further studies are required to assess health risks for humans.…”
Section: Introductionmentioning
confidence: 99%